2021
DOI: 10.11144/javeriana.sc26-1.dbit
|View full text |Cite
|
Sign up to set email alerts
|

Denitrifying bacteria in the limnetic zone of Lake Tota, Colombia

Abstract: The objective of study was to isolate and determine the identity of denitrifying bacteria from limnetic areas of Lake Tota (Colombian Andes) with and without rainbow trout production activities. We examined the relationships between the lake’s physicochemical factors (oxygen, nitrogen, and phosphorus content) and two bacterial communities (denitrifying bacteria and coliforms). Water samples were taken 20m below the surface from July to September at five limnetic zones; two of which were close to rainbow trout … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Stutzerimonas stutzeri is a Gram-negative, facultative anaerobic bacterium belonging to the Gammaproteobacteria that has been frequently reported to coexist with cyanobacterial species in eutrophic ecosystems ( 1 3 ). S. stutzeri is an important natural denitrifier, and studies have also shown its promising applicability in bioremediation, pollutant degradation, and wastewater treatment, owing to its rich repertoire of genes involved in the metabolism of organic and toxic compounds ( 4 6 ).…”
Section: Announcementmentioning
confidence: 99%
“…Stutzerimonas stutzeri is a Gram-negative, facultative anaerobic bacterium belonging to the Gammaproteobacteria that has been frequently reported to coexist with cyanobacterial species in eutrophic ecosystems ( 1 3 ). S. stutzeri is an important natural denitrifier, and studies have also shown its promising applicability in bioremediation, pollutant degradation, and wastewater treatment, owing to its rich repertoire of genes involved in the metabolism of organic and toxic compounds ( 4 6 ).…”
Section: Announcementmentioning
confidence: 99%
“…Studies suggest that naturally occurring microorganisms in fresh and saltwater play diverse roles in ecosystems and are essential to Earth’s biogeochemical cycles . Depending on the aquatic environment, microorganisms in lentic systems can thrive in the littoral zone, a region of a liquid body near the shoreline, well-lighted, shallow, and warmer than other regions of the water; limnetic zone, further away from the shore, colder and having sunlight only in the upper 100 feet or so; benthic zone, at depths without any oxygen and sunlight; subterranean systems, with varied salt concentrations and pH levels (acidophiles and alkaliphiles); salty water bodies, with higher salt concentration, (halophiles), higher pH, and lower nutrients; and hydrothermal vents and within biofilms, a grouping of cells surrounded by a polymer matrix providing a protective barrier to the external environment. The activity in these ecosystems may also vary seasonally, and by monitoring them continuously over a long time, a detailed account of the nutrient and gas cycling can be established .…”
Section: Introductionmentioning
confidence: 99%